2019
DOI: 10.1111/1346-8138.14771
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between rosacea and dietary factors: A multicenter retrospective case–control survey

Abstract: Although patients with rosacea often consult dermatologists for dietary factors that might be related to their skin disorders, few studies have been conducted to research the relationship between rosacea and dietary factors. The purpose of this study was to evaluate the potential relationship between rosacea and diet among the large Chinese population with rosacea, which would provide dietary guidelines for patients with rosacea. A multicenter case–control study was conducted. The feeding frequency 2 years bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 41 publications
2
33
0
5
Order By: Relevance
“…[9][10][11][12] Prevalence differences of rosacea around the world have been mainly attributed to skin phototypes and environmental factors (climate, ultraviolet [UV] exposure and lifestyle). 13 Regardless of racial differences in prevalence, sampling methodology and case criteria may also influence prevalence findings. Our study involved residents from communities of different socioeconomic strata to account for differences among participants and to give more representative results.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Prevalence differences of rosacea around the world have been mainly attributed to skin phototypes and environmental factors (climate, ultraviolet [UV] exposure and lifestyle). 13 Regardless of racial differences in prevalence, sampling methodology and case criteria may also influence prevalence findings. Our study involved residents from communities of different socioeconomic strata to account for differences among participants and to give more representative results.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the genetic background, other factors, including Demodex colonization, microbial stimuli, ultraviolet radiation, heat, dietary factors and stress, are considered to be related to this condition 13,14 . Other behavioral factors, including anxiety and depression, are found to be associated with rosacea 15 …”
Section: Introductionmentioning
confidence: 99%
“…34,35 On the other hand, there has been a growing debate about whether the caffeine or the temperature of the coffee is the actual culprit for exacerbation of rosacea. [34][35][36] The fact that increased risk of rosacea is also linked with caffeine containing beverages that are lukewarm or cool in temperature, has brought the idea of the association of caffeine and rosacea is not only heat related. 36 Moreover, paradoxically, in a recent study it has been shown that increased caffeine intake from coffee is conversely associated with the risk of rosacea in women.…”
Section: Coffee For Rosacea: the Good Or The Bad?mentioning
confidence: 99%
“…[34][35][36] The fact that increased risk of rosacea is also linked with caffeine containing beverages that are lukewarm or cool in temperature, has brought the idea of the association of caffeine and rosacea is not only heat related. 36 Moreover, paradoxically, in a recent study it has been shown that increased caffeine intake from coffee is conversely associated with the risk of rosacea in women. 37 Caffeine is a methylxanthine, which increases intracellular calcium stimulating the production of nitric oxide (NO).…”
Section: Coffee For Rosacea: the Good Or The Bad?mentioning
confidence: 99%
See 1 more Smart Citation